Perencanaan Strategis Sistem Informasi Di Sinode GKJ Menggunakan Enterprise Architecture Planning Framework - Monika Prianti; Frederik Samuel Papilaya (Universitas Bina Darma, 2021)
The GKJ Synod is one of the Church Foundations located in Salatiga which is an institution that focuses on the field of information data center and media services for the GKJ Synod. The Salatiga GKJ Synod currently has a system but still has problems with Information System problems that have not been implemented optimally, so there are often obstacles when doing work. Because it does not run quickly and well, therefore an Information System Strategic Planning is needed, this research aims to be able to help the business processes contained in the GKJ Synod implement information systems in the organization to run well. The purpose of this research is to propose and plan using the method Enterprise Architecture Planning. Enterprise Architecture Planning (EAP) is the process of defining the architecture in the use of information systems to support the architecture implementation plan. By using the approach, the Enterprise Architecture Planning (EAP)method can help the GKJ Salatiga synod to plan data quality oriented to business needs in order to achieve and support business goals for agencies and organizations, besides that, the advantages of using Enterprise Architecture Planning are a supporting method for making decisions and good planning for an organization.